183k views
5 votes
Help me ASAP!!!!!
Thank you!!!!!

Help me ASAP!!!!! Thank you!!!!!-example-1
User Ergo
by
5.3k points

1 Answer

5 votes

Call the amount Paul as have x, Helen as have y.

x + y = 90
(y + 16) - (x - 16) = 14 [ y + 16 = helen receives 16, x - 16 = paul lose 16, (y+16) - (x-16) = 14 -> the difference between their money at that moment is 14. ]

Break bracket : y + 16 - x + 16 = 14

y - x + 32 = 14
y - x = -18

-> x - y = 18

So, x + y = 90, x - y = 18

-> x = (90+18)/2 = 54
y = 90 - 54 = 36

Recheck :

When Paul gives Helen 16, then Paul has 54 - 16 = 38
Helen has 36 + 16 = 52


That is 14 less, so it satisfies the question.

User Eran Chetzroni
by
5.1k points